Cationic host defense peptides; novel antimicrobial therapeutics against Category A pathogens and emerging infections. (3rd July 2016) - Findlay, Fern; Proudfoot, Lorna; Stevens, Craig; Barlow, Peter G.
Abstract : Cationic Host Defense Peptides (HDP, also known as antimicrobial peptides) are crucial components of the innate immune system and possess broad-spectrum antibacterial, antiviral, and immunomodulatory activities. They can contribute to the rapid clearance of biological agents through direct killing of the organisms, inhibition of pro-inflammatory mediators such as lipopolysaccharide, and by modulating the inflammatory response to infection. Category A biological agents and materials, as classified by the United States National Institutes for Health, the US Centers for Disease Control and Prevention, and the US Department of Homeland Security, carry the most severe threat in terms of human health, transmissibility, and preparedness. As such, there is a pressing need for novel frontline approaches for prevention and treatment of diseases caused by these organisms, and exploiting the broad antimicrobial activity exhibited by cationic host defense peptides represents an exciting priority area for clinical research. This review will summarize what is known about the antimicrobial and antiviral effects of the two main families of cationic host defense peptides, cathelicidins, and defensins in the context of Category A biological agents which include, but are not limited to; anthrax ( Bacillus anthracis ), plague ( Yersinia pestis ), smallpox ( Variola major ), tularemia ( Francisella tularensis ). In addition, we highlight priority areas, particularly emerging viral infections, where more extensive research is urgently required.